Eye Health Problems Related to Prolonged Exposure to Electronic Devices - Nur Mahmudah Elmaje; Dahlan Latuconsina; Andiar Putra (Magenta Journal De Healthymedi, 2026)
The increasing dependence on electronic devices in occupational, educational, and recreational activities has intensified concerns regarding eye health problems associated with prolonged screen exposure. This study aimed to examine the prevalence of visual discomfort among adult electronic device users and to identify behavioral, environmental, and individual factors influencing ocular health outcomes. A quantitative cross-sectional design was employed involving 300 respondents aged 18 years and above who routinely used electronic devices for at least two hours daily. Data were collected through structured questionnaires assessing screen exposure patterns, ergonomic conditions, behavioral practices, and self-reported eye health symptoms. The findings revealed a high prevalence of digital eye strain symptoms, particularly eye fatigue, dry eyes, blurred vision, and headaches. Prolonged screen exposure exceeding six hours daily emerged as the strongest predictor of visual discomfort, while irregular visual breaks, excessive screen brightness, close viewing distance, and corrective lens use further increased symptom prevalence. The novelty of this study lies in its multidimensional analytical framework integrating behavioral, environmental, and physiological determinants within broader non-clinical populations. The findings highlight the importance of integrated preventive strategies combining ergonomic improvements, digital-wellbeing education, and institutional support to promote sustainable and healthier digital technology use.